A Yellow Box with a Key Switch and a 1/4″ TRS Balanced Audio Output - Koutsomichalis, Marinos (My University, 2021)
This short article presents a reductionist infra-instrument. It concerns a yellow die-cast aluminium box only featuring a key switch and a 1/4” TRS balanced audio output as its UI. On the turn of the key, the device performs a certain poem in Morse code and via very low frequency acoustic pulses; in this way, it transforms poetry into bursts of intense acoustic energy that may resonate a hosting architecture and any human bodies therein. It is argued that the instrument functions at the very same time as a critical/speculative electronic object, as an ad-hoc performance instrument, and as a piece of (conceptual) art on its own sake.
Keywords: Critical design; Speculative design; Infra-instrument; Hertzian Instrument; Αd-hoc instrument